OVERVIEW OF A SOFTWARE PRODUCT “ANYLOGIC” USED IN TRAINING OF STUDENTS IN GENERAL ENGINEERING: OVERVIEW OF A SOFTWARE PRODUCT “ANYLOGIC” USED IN TRAINING OF STUDENTS IN GENERAL ENGINEERING - Antonov, Anton; Neikova, Krasimira (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
The design of a complex logistics system requires many people and resources to support the design of the various elements and stages, that can be used for specialized software products. One of the software that can be used for designing logistic systems such as warehouses, storage equipment, industrial buildings, transport schemes for road, rail, sea, air and combined transport is “AnyLogic” . Therefore the aim of this work is to present “AnyLogic” software product and its application in education of students in general engineering.